Analisis Pengolahan Sampah Restoran di Kota Jambi - Umniah Hanesti; Dwi Nowo Martono; Sri Setiawati Tumuyu (Universitas Riau, 2024)
Restaurants are one of the most waste-producing sectors after households, on average a restaurant produces 25000– 75000 pounds of waste per year. Waste generation in Indonesia has now reached 19,447,761.38 tons/year. Jambi City is one of the cities in Indonesia with the amount of waste generated as much as 437.50 tons/day. This study aims to analyze the generation and composition of waste generated from restaurants in Jambi City and to analyze restaurant waste processing in Jambi City. Methods for collecting and measuring waste generation and composition according to SNI 19-3964-1994, field observations, and also interviews. Based on the research results, it was found that restaurants produce various types of waste, restaurant waste is dominated by food waste, reaching 88.89%, then plastic waste 6.41%, and residual waste 3.61%. The average waste generated by restaurant X was 309.61 kg/day and had a density of 256.96 kg/m3. While the total waste generation in Jambi City is 115.17 tons/day. Therefore, it is necessary to process restaurant waste in order to reduce the amount of waste that will be disposed of in the landfill, including by composting, processing waste using Black Soldier Fly (BSF), and also by cooperate with livestock feed.